2019
DOI: 10.7150/jca.28959
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin based induction chemotherapy modified by ERCC1 improved the outcome of young adults with locally advanced oral squamous cell carcinoma

Abstract: Objective: To evaluate the efficacy of induction chemotherapy in young adults with locally advanced oral squamous cell carcinoma (OSCC) and the usefulness of ERCC1 as a prognostic indicator. Methods: A total of 156 young adults with locally advanced OSCC were retrospectively analyzed from May 2007 to May 2017. Cisplatin based induction chemotherapy followed by surgery and upfront surgery were the primary treatment options for locally advanced OSCC. ERCC1 was evaluated by immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 33 publications
1
0
0
Order By: Relevance
“…However, other studies have reported that the incidence in young adults was increased (Shiboski et al, 2005, Patel et al, 2001. Tobacco or alcohol use may not be the etiology of OSCC in young adults, Gong et al (2019) study has demonstrated that only 7% (11/156) patients were heavy smokers [11]. Our results were similar to previous results; we have only 9 out of 25 patients (36%) who were smokers but we detected other factors as chronic irritation by sharp dental problems in 13 cases (52%).…”
Section: Discussionsupporting
confidence: 89%
“…However, other studies have reported that the incidence in young adults was increased (Shiboski et al, 2005, Patel et al, 2001. Tobacco or alcohol use may not be the etiology of OSCC in young adults, Gong et al (2019) study has demonstrated that only 7% (11/156) patients were heavy smokers [11]. Our results were similar to previous results; we have only 9 out of 25 patients (36%) who were smokers but we detected other factors as chronic irritation by sharp dental problems in 13 cases (52%).…”
Section: Discussionsupporting
confidence: 89%